2001
DOI: 10.1097/00003246-200112000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing timing of ventricular defibrillation

Abstract: AMSA has the potential for guiding more optimal timing of defibrillation without adverse interruption of cardiopulmonary resuscitation or the delivery of unsuccessful high energy electrical shocks that contribute to postresuscitation myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 29 publications
1
75
0
Order By: Relevance
“…AMSA is a frequency weighted mean of the spectral amplitudes of the VF waveform [27], and it is the most extensively studied of all predictors [12]. To compute AMSA, the signal was Hamming windowed, and its fast Fourier transform (FFT), X(k), was computed using a N FFT = 2048 point FFT.…”
Section: Classical Shock Outcome Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMSA is a frequency weighted mean of the spectral amplitudes of the VF waveform [27], and it is the most extensively studied of all predictors [12]. To compute AMSA, the signal was Hamming windowed, and its fast Fourier transform (FFT), X(k), was computed using a N FFT = 2048 point FFT.…”
Section: Classical Shock Outcome Predictorsmentioning
confidence: 99%
“…Consequently, a plethora of VF-waveform features have been proposed to predict defibrillation success and to optimize treatment decisions [23][24][25][26]. These quantitative measures include the classical amplitude, slope or spectral analyses of VF [23,27], but also features derived from non-linear dynamics, such as: fractal dimension [28], Hurst exponents [28], scaling exponents [20], detrended fluctuation analysis [29] or Poincare-plot analysis [30]. These later approaches suggest that quantifying the VF waveform regularity and/or predictability through non-linear metrics may be an adequate way to predict defibrillation success.…”
Section: Introductionmentioning
confidence: 99%
“…In a porcine model, the median frequency (CF correspondent) improved with CPR with no significant change in the amplitude (ENRG correspondent). 8 In other pig models, both Marn-Pernat et al 11 and Povoas et al 12 reported that AMSA improved with CPR. Marn-Pernat et al 11 demonstrated that both AMSA and ROSC increased with an increased duration of CPR.…”
Section: Discussionmentioning
confidence: 97%
“…The amplitude spectrum relationship (AMSA) emphasizes the high-frequency characteristics of the waveform by computing the sum of each frequency component amplitude weighted by the corresponding frequency. 11,12 Centroid frequency (CF) quantifies the frequency characteristics of the waveform by computing the frequency corresponding to the point of mass in the spectrum. 9 CF emphasizes the low-frequency content of VF.…”
Section: Calculating and Evaluating Predictors Of Roscmentioning
confidence: 99%
See 1 more Smart Citation